A Socio-Psychological Model of Values Among Different Generations in Modern Russian Society - Aleksandr M. Rikel; Svetlana V. Dorenskaya (Rossijskij psihologičeskij žurnal., 2017)
Introduction. The study (a) addresses value hierarchy among different generations in modern Russia and (b) concentrates on how different generations perceive other groups of people and also people of their own age cohort. Different generations of modern Russia were the object of the study; their values became the subject of the study. The paper provides an analysis of various approaches to understanding the “generation” term. The novelty of the research lies in constructing models of how modern Russian generations perceive themselves and each other on the basis of value dispositions. Methods. These were M. Rokich’s “Value Orientation” technique, the author’s questionnaire for identifying how generations perceive each other, and the author’s questionnaire for revealing values declared by culture. The study involved 100 people (40 men and 60 women born between 1948 and 1997). Results. The statistical analysis revealed a hierarchy of values for each of the three studied generations. Significant differences in the hierarchies and mutual perception of generations depend on value orientations. Respondents with greater age difference differed the most. Generations perceived each other according to values declared by culture in each group of respondents. Discussion. Cultural and socio-psychological fundamentals for the formation of generational groups, describing a generational “gap” in transmission of values, helped to interpret the results.The results confirmed the logic of K. Mannheim, M. Mead, E. Toffler, and also recent studies. The value intergenerational gap predicts reduction in age limits to 10–15 years within a single generational cohort. Differences in basic values, attitude to family, work, material and civic values determine how generations perceive each other and also the value gap. Generational groups perceive each other being guided by these values.